Evaluation of Cytotoxicity Effects of Chalcone Epoxide Analogues as a Selective COX-II Inhibitor in the Human Liver Carcinoma Cell Line - Pouran Makhdoumi; Afshin Zarghi; Bahram Daraei; Gholamreza Karimi (Korean Pharmacopuncture Institute, 2017)
Objectives: Study of the mechanisms involved in cancer progression suggests that cyclooxygenase enzymes play an important role in the induction of inflammation, tumor formation, and metastasis of cancer cells. Thus, cyclooxygenase enzymes could be considered for cancer chemotherapy. Among these enzymes, cyclooxygenase 2 (COX-2) is associated with liver carcinogenesis. Various COX-2 inhibitors cause growth inhibition of human hepatocellular carcinoma cells, but many of them act in the COX-2 independent mechanism. Thus, the introduction of selective COX-2 inhibitors is necessary to achieve a clear result. The present study was aimed to determine the growth-inhibitory effects of new analogues of chalcone epoxide as selective COX-2 inhibitors on the human hepatocellular carcinoma (HepG2) cell line. Methods: Estimation of both cell growth and the amount of prostaglandin E2 (PGE2) production were used to study the effect of selective COX-2 inhibitors on the hepatocellular carcinoma cell. Cell growth determination has done by MTT assay in 24 h, 48 h and 72 h, and PGE2 production has estimated by using ELYSA kit in 48 h and 72 h. Results: The results showed growth inhibition of the HepG2 cell line in a concentration and time-dependent manner, as well as a reduction in the formation of PGE2 as a product of COX-2 activity. Among the compounds those analogues with methoxy and hydrogen group showed more inhibitory effect than others. Conclusion: The current in-vitro study indicates that the observed significant growth-inhibitory effect of chalcone-epoxide analogues on the HepG2 cell line may involve COX-dependent mechanisms and the PGE2 pathway parallel to the effect of celecoxib. It can be said that these analogues might be efficient compounds in chemotherapy of COX-2 dependent carcinoma specially preventing and treatment of hepatocellular carcinomas.